FACTOR RELATED TO EPISIOTOMY PRACTICE : SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
An episiotomy is a surgical operation used toward the end of the second stage of labor to make an incision on the perineum and widen the vaginal aperture in order to assist vaginal birth. 1 It has developed into one of the obstetric procedures that are carried out the most frequently worldwide since it was first documented in the 10th century. It lessens the likelihood that the woman or her newborn baby may experience problems during labor and aids in smoother delivery. The World Health Organization (WHO) recommends a maximum ten percent episiotomy rate for all normal deliveries. An effort was made to fill a gap in the field under consideration regarding the updating of risk factors related to perineal incisions and the search for new ones that take into account their causes (medical indications). According to the conducted study, there were several independent risk factors for episiotomy during labor, including the first delivery, a longer second stage of labor, status after a cesarean section, epidural anesthesia, male gender, and a higher birth weight. A substantial protective factor against the necessity for an episiotomy was giving birth at a birth center. According to research, nullipara and age under 20 are the two main reasons why an episiotomy is necessary. The requirement for an episiotomy and the likelihood of complications are both increased by labor's first and second stage labor being prolonged.